PWE-044 Exploring the efficacy of weight-based dosing of thiopurine therapy in relation to metabolite levels at week 12 in patients with inflammatory bowel disease. (22nd June 2015) - Cox, R; Lee, H; Willert, R
Abstract : Introduction: Traditionally patients commencing on thiopurine therapy in IBD have been dosed according to their body weight with data showing less than 70% achieve long term steroid free remission. 1 The ability to measure thiopurine metabolites has shown that 6-thioguanine nucleotide (6-TGN) levels inversely correlate with disease activity and patients with sub-therapeutic concentrations are less likely to achieve remission. Also very high 6-TGN concentrations risk myelotoxicity and hepatic nodular regernative hyperplasia whilst 6-methyl mercaptopurine (6-MMP) concentrations above 5700 pmol/8 × 10 8 correlate with hepatotoxicity. 2 Method: The primary aim of this study was to assess how effective weight based dosing is in achieving therapeutic 6-TGN levels after 12 weeks of therapy, in patients with normal TPMT activity, when commencing thiopurines for the first time at our institution for both Crohn's and Ulcerative Colitis between Oct 2013 and July 2014. The incidence of potentially toxic thiopurine levels was also assessed along with symptoms, MCV, LFTs and disease activity indicies. All patients with normal TMPT levels were dosed at 2.5 mg/kg (azathioprine) or 1.5 mg/kg (mercaptopurine) with any dose adjustments made clinically based on blood results and symptoms. Results: From 37 patients with normal TPMT activity (19 male) at week 12 on stable thiopurine weight based therapy 15 (41%) did not achieve therapeutic 6-TGN concentrations. 7 (19%) were under-dosed, 6 (16%) were overdosed and 2 (6%) preferentially metabolised to excessive 6-MMP levels. Disease activity indices, faecal calprotectin, MCV and routine blood monitoring for leucopenia and abnormal LFTs did not consistently correlate with metabolite levels at week 12. Conclusion: Weight-based dosing does not appear to be an accurate method for establishing patients on thiopurine maintenance therapy and this may explain the previous perceived lack of efficacy of thiopurines in a significant number of patients. MCV cannot be used as a surrogate for sufficient 6-TGN levels at week 12 and of the 2 "shunters" neither had significantly abnormal LFTs highlighting the need to identify these group using metabolite monitoring to enable allopurinol co-prescribing. The lack of correlation with disease activity indicies at week 12 likely reflects the patients having recently completed an induction course of steroids and that thiopurines themselves are not induction agents. Starting patients on weight-based dosing plus metabolite monitoring at week 12 to achieve therapeutic ranges may increase long term maintenance rates and increase the safety of treatment by preventing toxicity and a larger long term outcome study is warranted. Disclosure of interest: None Declared. References: D'Haens G, et al . 1999;50:667–71 Moreau AC, et al . 2014;20:464–71